Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Turnover Intention Pada Karyawan Jasa Elektroplating PT Tetra Mitra Sejahtera: Influence of Workload and Work Environment on Turnover Intention among Electroplating Service Employees at PT Tetra Mitra Sejahtera - Wulandari, Asti; Fadilla, Arif (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the influence of Workload and Work Environment on Turnover Intention among Electroplating Service Employees of PT Tetra Mitra Sejahtera. This study uses a quantitative method. To examine the effect, the scale range analysis technique and multiple linear regression analysis were used with data collection techniques in the form of primary data obtained through questionnaires distributed to permanent employees of PT Tetra Mitra Sejahtera. This study uses a saturated sampling technique with a sample size of 73 respondents. The results of this study explain that partially there is a significant positive effect between workload and turnover intention. The work environment also has a significant negative effect partially on turnover intention. Workload and work environment simultaneously affect turnover intention by 31.8% while the remaining 68.2% is influenced by other variables or factors not studied. Keywords : Workload, Work Environment, Turnover Intention